Cristae junction as a fundamental switchboard for mitochondrial ion signaling and bioenergetics. (January 2022) - Gottschalk, Benjamin; Madreiter-Sokolowski, Corina T.; Graier, Wolfgang F.
Highlights: Cristae junction represent a diffusion barrier for Ca 2+ and H + . Permeability of the cristae junction for ions, proteins and metabolites is controlled by OPA1 and MICU1. Ca 2+ dependent cristae junction regulation is mediated by MICU1. Disruption of the cristae junction result in Ca 2+ overload via constitutively active MCU located in the cristae membrane. OPA1 and MICU1 shape the cristae morphology to adapt to Ca 2+ signals and metabolic challenges. Abstract: OPA1 and MICU1 are both involved in the regulation of mitochondrial Ca 2+ uptake and the stabilization of the cristae junction, which separates the inner mitochondrial membrane into the interboundary membrane and the cristae membrane. In this mini-review, we focus on the synergetic control of OPA1 and MICU1 on the cristae junction that serves as a fundamental regulator of multiple mitochondrial functions. In particular, we point to the critical role of an adaptive cristae junction permeability in mitochondrial Ca 2+ signaling, spatial H + gradients and mitochondrial membrane potential, metabolic activity, and apoptosis. These characteristics bear on a distinct localization of the oxidative phosphorylation machinery, the Fo F1 -ATPase, and mitochondrial Ca 2+ uniporter (MCU) within sections of the inner mitochondrial membrane isolated by the cristae junction and regulated by proteins like OPA1 and MICU1. We specifically focus on the impact of MICU1-regulated cristae junction on the activity and distribution of MCU within the complex ultrastructure of mitochondria. Graphical abstract: Image, graphical abstract